Transcriptional enhancement by GATA1-occupied DNA segments is strongly associated with evolutionary constraint on the binding site motif - Cheng, Yong; King, David C.; Dore, Louis C.; Zhang, Xinmin; Zhou, Yuepin; Zhang, Ying; Dorman, Christine; Abebe, Demesew; Kumar, Swathi A.; Chiaromonte, Francesca; Miller, Webb; Green, Roland D.; et al.

(untitled) (Genome Research, 2008)
Tissue development and function are exquisitely dependent on proper regulation of gene expression, but it remains controversial whether the genomic signals controlling this process are subject to strong selective constraint. While some studies show that highly constrained noncoding regions act to enhance transcription, other studies show that DNA segments with biochemical signatures of regulatory regions, such as occupancy by a transcription factor, are seemingly unconstrained across mammalian evolution. To test the possible correlation of selective constraint with enhancer activity, we used chromatin immunoprecipitation as an approach unbiased by either evolutionary constraint or prior knowledge of regulatory activity to identify DNA segments within a 66-Mb region of mouse chromosome 7 that are occupied by the erythroid transcription factor GATA1. DNA segments bound by GATA1 were identified by hybridization to high-density tiling arrays, validated by quantitative PCR, and tested for gene regulatory activity in erythroid cells. Whereas almost all of the occupied segments contain canonical WGATAR binding site motifs for GATA1, in only 45% of the cases is the motif deeply preserved (found at the orthologous position in placental mammals or more distant species). However, GATA1-bound segments with high enhancer activity tend to be the ones with an evolutionarily preserved WGATAR motif, and this relationship was confirmed by a loss-of-function assay. Thus, GATA1 binding sites that regulate gene expression during erythroid maturation are under strong selective constraint, while nonconstrained binding may have only a limited or indirect role in regulation.